2020
DOI: 10.1080/10413200.2020.1792583
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of sport-based life skills programs for young people: The quality of design and evaluation methods

Abstract: Over the past two decades, researchers have reported positive life skills outcomes for young people participating in sport-based life-skills programs. However, to date, there has been a lack of consideration in the literature regarding the quality of the programs designed and the evaluation methods adopted. Therefore, we conducted a systematic review of the life skills literature to: (a) assess the quality of sport-based life skills program design and evaluation methods; and (b) identify characteristics relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
(164 reference statements)
0
9
0
Order By: Relevance
“…Our results on correlations between coaches’ needs–supportive behavior, total need satisfaction, and generalization of psychosocial skills in competitive sports were consistent with the insights of Bean et al [ 28 ], Cronin et al [ 42 ], and Cronin, Ellison et al [ 43 ] that BNS mediated the associations between autonomy-supportive coaching and youth sports and PE participants’ development of life skills. Few quantitative theory-based studies have investigated the development of life skills [ 8 , 23 , 47 ]. Our findings support Hodge et al’s [ 23 ] conceptual model for life skills development and their proposition by a quantitative approach and suggest that LDI/BNT and SDT (i.e., coaches’ needs–supportive behavior and BNS) can serve as a theoretical framework for further investigating life skills development in competitive sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results on correlations between coaches’ needs–supportive behavior, total need satisfaction, and generalization of psychosocial skills in competitive sports were consistent with the insights of Bean et al [ 28 ], Cronin et al [ 42 ], and Cronin, Ellison et al [ 43 ] that BNS mediated the associations between autonomy-supportive coaching and youth sports and PE participants’ development of life skills. Few quantitative theory-based studies have investigated the development of life skills [ 8 , 23 , 47 ]. Our findings support Hodge et al’s [ 23 ] conceptual model for life skills development and their proposition by a quantitative approach and suggest that LDI/BNT and SDT (i.e., coaches’ needs–supportive behavior and BNS) can serve as a theoretical framework for further investigating life skills development in competitive sports.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the studies highlighted above and expanding upon Cronin et al’s and Cronin, Ellison et al’s research [ 42 , 43 ], the current study sought to examine how coaches’ needs–supportive and –thwarting behaviors (i.e., competence and relatedness, in addition to autonomy bats), and BNS and BNF are either positively or negatively related to collegiate athletes’ generalization of psychosocial skills in competitive sports. This is a novel addition to the research literature, as few theory-based studies have investigated the process of life skills development through sports using a quantitative approach [ 8 , 23 , 47 ]. Focusing on the generalization of psychosocial skills in competitive sports, this study adds to our understanding of how exactly collegiate athletes develop their life skills within the context of competitive sports.…”
Section: Introductionmentioning
confidence: 99%
“…Using the COM-B measures, this research identifies specific antecedents of behavior that inform researchers on how the TCW impacted the coaches. Additionally, in their systematic review of PYD-focused sport programs, Williams et al 53 note that existing evaluative studies in the sport context overuse qualitative measures post-intervention and do not incorporate control groups to better contextualize changes observed post-program. The preference for qualitative approaches may be attributable to a lack of available, validated sport-specific measures for researchers, which is identified as a persisting issue in the sport literature.…”
Section: Discussionmentioning
confidence: 99%
“…The preference for qualitative approaches may be attributable to a lack of available, validated sport-specific measures for researchers, which is identified as a persisting issue in the sport literature. 53,54 As such, this research advances the sport coaching science threefold: (a) provides a preliminary understanding of elements that influence the coaches’ use of transformational coaching behaviors, 22 (b) uses a comparison group at pre-and post-intervention time points, and (c) demonstrates the novel application of behavior change theory to address a gap in the sport literature by proposing an alternative approach to evaluation in the sports science context.…”
Section: Discussionmentioning
confidence: 99%
“…One key aspect of Positive Youth Development (PYD) is the area of life skills development through sports and physical education (PE) ( Goudas and Giannoudis, 2008 ; Mossman et al, 2021 ). Life skills are described as functional skills that individuals develop and use effectively in one context (such as sports, physical education, home, and community) and that are then used effectively in other contexts ( Williams et al, 2020 ). Others have further suggested that life skills are adaptive and positive behaviors that empower individuals to deal effectively with the demands and challenges of everyday life ( Singla et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%